NOTES ON EGGS, LARVJE AND JUVENILES OF FISHES FROM INDIAN WATERS 1. Xiphias Gladius Linnaeus - Jones, S (Indian Journal of Fisheries, 2016)
Since December 1957 plankton collections were being made from the WestCoast and Wadge Bank during the cruises of the Research Vessel " Kalava "of the Indo-Norwegian Project which is utilised by the Central MarineFisheries Research Station for oceanographic and fisheries investigations on aco-operative basis. During a cruise to Minicoy and some other islands of theLaccadive Archipelago in February 1958 I was able to collect a number ofeggs, larvÂ£e and juveniles of fishes. In the meanwhile I have had also theoccasion to examine the larval and juvenile fishes collected from the IndianOcean by the Danish " Dana " expedition of 1928-30 which were placedat my disposal some time ago for study. While the " Dana" collectionwill be treated separately, reference will be made to it whenever comparisonis necessary, when dealing with other collections.